Indocyanine Green Nanoparticles for Theranostic Applications - Sheng, Zonghai; Hu, Dehong; Xue, Miaomiao; He, Meng; Gong, Ping; Cai, Lintao (Nano-Micro Letters, 2013)
Theranostics is a concept that integrated imaging and therapy. As an emerging field, it embraces multiple techniques to arrive at an individualized treatment purpose. Indocyanine green (ICG) is a near infrared dye that has been approved by Food and Drug Administration (FDA) in USA for the use in indicator-dilution studies in humans. ICG nanoparticles (NPs) have attracted much attention for its potential applications in cancer theranostics. This review focuses on the preparation, application of ICG NPs for in vivo imaging (fluorescent imaging and photoacoustic imaging) and therapeutics (photothermal therapy, photodynamic therapy and photoacoustic therapy), and future directions based on recent developments in these areas. It is hoped that this review might provide new impetus to understand ICG NPs for cancer theranostics.